Updated ME/CFS prevalence estimates reflecting post-COVID increases and associated economic costs and funding implications. Issue 2 (3rd April 2022) - Mirin, Arthur A.; Dimmock, Mary E.; Jason, Leonard A.
ABSTRACT: In this article, we update our earlier analyses of myalgic encephalomyelitis / chronic fatigue syndrome (ME/CFS) economic impact and its National Institutes of Health (NIH) funding versus disease burden, taking into account the anticipated new cases of ME/CFS resulting from COVID-19. Prior to the COVID pandemic, we estimated a United States ME/CFS prevalence of 1.5 million and an annual economic impact of 36–51 billion. Now, due to COVID and its resulting post-acute sequalae, we estimate total ME/CFS prevalence could rise to between five and nine million. This would incur an annual U.S. economic impact of 149 to 362 billion in medical expenses and lost income, exclusive of other costs, such as disability benefits, social services, and lost wages of caretakers. NIH funding for ME/CFS research would need to expand from the current amount of 15 million per year to approximately 472–600 million annually, up to a 40-fold increase, to be commensurate with that of similarly burdensome diseases.